2019
DOI: 10.1530/edm-19-0099
|View full text |Cite
|
Sign up to set email alerts
|

Mixed gangliocytoma-pituitary adenoma containing GH and GHRH co-secreting adenoma cells

Abstract: Summary A 67-year-old woman with a past history of type 2 diabetes mellitus presented with worsening glycemic control. She had some acromegaly symptoms and magnetic resonance imaging demonstrated a pituitary tumor. Endocrinological examination found the resting growth hormone (GH) level within the normal range, but elevated insulin-like growth factor 1 level. A 75 g oral glucose tolerance test showed inadequate suppression of nadir GH levels. Acromegaly due to GH-secreting pituitary tumor was diagnosed. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The phenomena in pituitary tumors exhibiting co-secretion of hypothalamic upstream hormones and pituitary downstream hormones in the same tumor cell have been reported on rare occasions. In acromegaly, co-secreting GH-GHRH-producing adenoma has been reported in cases of both pure pituitary adenoma and adenomatous components in MGA ( 76 , 77 ). Moreover, some investigations have demonstrated that GHRH can synthesize not only in the normal pituitary gland, but also concurrently in somatotroph adenoma cells ( 78 , 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phenomena in pituitary tumors exhibiting co-secretion of hypothalamic upstream hormones and pituitary downstream hormones in the same tumor cell have been reported on rare occasions. In acromegaly, co-secreting GH-GHRH-producing adenoma has been reported in cases of both pure pituitary adenoma and adenomatous components in MGA ( 76 , 77 ). Moreover, some investigations have demonstrated that GHRH can synthesize not only in the normal pituitary gland, but also concurrently in somatotroph adenoma cells ( 78 , 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…The second theory is that heterotopic hypothalamic neurons within the adenohypophysis can produce stimulatory peptides (for example growth hormone releasing hormone) leading to hyperplasia and subsequent neoplastic transformation of adenohypophysial cells. A recent publication by Teramoto et al [13] revealed colocalization of GH and GH-releasing hormone (GHRH) in pituitary adenoma cells. The third hypothesis suggests the pituitary adenoma as the initial lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial report of the possible association between the neuroendocrine functional tumor and acromegaly, suggested by Altmann et al. in 1959, around 170 cases of suspected ectopic acromegaly have been described in literature to date, mostly as case reports ( 4 , 6 , 9 – 21 ). To our best knowledge, only 19 cases were described as caused by an ectopic source of GH ( 22 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…The term ‘ectopic’ is used in a broader sense in this review, applying not only to its most common meaning of an abnormal localization, but also basically to the secretion of a hormone by a tissue that does not produce it under physiological circumstances ( 5 ). Therefore, GHRH-secreting pituitary gangliocytoma will also be included in the review, as they fall under given definition ( 6 ). Ectopic acromegaly clinical features are indistinguishable from those of acromegaly caused by a pituitary somatotropinoma ( 7 ).…”
Section: Introductionmentioning
confidence: 99%